2021
DOI: 10.1631/jzus.b2100130
|View full text |Cite|
|
Sign up to set email alerts
|

Low-intensity pulsed ultrasound ameliorates angiotensin II-induced cardiac fibrosis by alleviating inflammation via a caveolin-1-dependent pathway

Abstract: Objective: Cardiac hypertrophy and fibrosis are major pathological manifestations observed in left ventricular remodeling induced by angiotensin II (AngII). Low-intensity pulsed ultrasound (LIPUS) has been reported to ameliorate cardiac dysfunction and myocardial fibrosis in myocardial infarction (MI) through mechano-transduction and its downstream pathways. In this study, we aimed to investigate whether LIPUS could exert a protective effect by ameliorating AngII-induced cardiac hypertrophy and fibrosis and if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…As a safe and non‐invasive approach, LIPUS has shown great potential in tissue repair and resolution of inflammation in various diseases 32–35 . Of note, the therapeutic effects of LIPUS on cardiovascular diseases have been reported in recent years 10–14 . In our present study, we showed that LIPUS therapy provided a great benefit in both acute and chronic DOX injury models, including the improvement of cardiac contractile function, the attenuation of myocardial injury and cellular apoptosis, as well as the alleviation of oxidative stress and cardiac fibrosis.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…As a safe and non‐invasive approach, LIPUS has shown great potential in tissue repair and resolution of inflammation in various diseases 32–35 . Of note, the therapeutic effects of LIPUS on cardiovascular diseases have been reported in recent years 10–14 . In our present study, we showed that LIPUS therapy provided a great benefit in both acute and chronic DOX injury models, including the improvement of cardiac contractile function, the attenuation of myocardial injury and cellular apoptosis, as well as the alleviation of oxidative stress and cardiac fibrosis.…”
Section: Discussionsupporting
confidence: 59%
“…8,9 Notably, LIPUS has shown great therapeutic potential in cardiovascular diseases such as myocardial infarction, 10 cardiac fibrosis, 11,12 viral myocarditis, 13 and heart failure with preserved left ventricular ejection fraction. 14 The molecular mechanisms of LIPUS therapy mainly involve regulations of oxidative stress, 12 inflammation [11][12][13] and endothelial function. 10,14 Interestingly, a recent study has demonstrated that brief exposure to LIPUS was sufficient to eliminate paclitaxel treatment-induced cytotoxicity, and might provide a new strategy to counter chemotherapyinduced peripheral neuropathy and alopecia.…”
mentioning
confidence: 99%
“…In the heart system, Zhao et al demonstrated that LIPUS prevents hypoxia-induced cardiac fibrosis through HIF-1α/DNMT3a pathway via a TRAAKdependent manner [61]. Their team also discovered that LIPUS could ameliorate angiotensin II-induced cardiac fibrosis by alleviating inflammation via a caveolin-1-dependent pathway [62]. In our study, various histological and behavioral functional indicators have been evaluated in detail and specific mechanisms have been elucidated by which LIPUS regulates the immune microenvironment of skeletal muscle from an immunological perspective.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is necessary to find an effective therapy to reduce joint capsule fibrosis during remobilization. Recently, the role of LIPUS in anti-fibrosis has received great attention (Aibara et al 2020; Liao et al 2021; Zhao et al 2021). Herein, we demonstrated that LIPUS can suppress anterior knee joint capsule fibrosis and arthrogenic contracture through inhibiting TGF-β1/Smad signaling pathway during remmobilization, thus indicating the potential of LIPUS as a novel therapeutic method for joint contracture.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LIPUS prevented endothelial-mesenchymal transitions by decreasing ROS accumulation and enhancing PI3K signaling cascade activation in human aortic endothelial cells. Importantly, the role of LIPUS in anti-fibrosis is well documented in myocardial infarction, osteoarthritis and hypertensive nephropathy, etc (Liao et al 2021; Zuo et al 2021; Zhao et al 2021). However, there are currently no previous reports investigating the curative effect of LIPUS on arthrogenic contracture and joint capsule fibrosis during immobilization or remobilization.…”
Section: Introductionmentioning
confidence: 99%